Dukungan Manajemen dalam Upaya Transformasi Digital Rekam Medis Elektronik - Sri Lestari; Rizkiyatul Amalia (Politeknik Negeri Jember, 2023)
Information Systems in health care facilities consist of several subsystems that are integrated with each other to support sustainable development (SDGs). One of them is the Electronic Medical Record (RME). The implementation of RME at Dr. Gondo Suwarno Hospital, Semarang Regency (RSGS) so far is in the form of SIMRS which is used only for transasional activities. The implementation encountered several obstacles including manual registration verification in the system, difficulties in retrieving report data due to the system between units that are not integrated and features that are not adequate user needs. Research was conducted to determine the influence of organization / management as an intervining variable on RME readiness. This study was conducted using sequential explanatory through questionnaires and interviews with respondents, namely system users. Data is processed quantitatively using SmartPLS and qualitative. Respondents consisted of 65 SIMRS users. The results showed P-Values of 0.246 on system quality against organizational structure. The test indirectly shows the quality of the system against RME readiness through the organizational structure with P-Values 0.256 and the organizational structure against RME readiness using systems with P-Values 0.464. Management is expected to be able to examine human resources, service models and vendors to be selected in the system development process.